The orthographic factor in phonologica. awareness with re.ation to reading pragna - V, Gokani (Journal of All India Institute of Speech and Hearing)
The present study was planned to compare the extent of relationship between phonological awareness and orthographic features in learning to read. Sixty children all coming from Gujarati speaking families were selected as subjects from two schools in Bombay. These children were administered a test of listening comprehension, word reading (English medium) and word recognition (Gujarati medium) and measures of speech segmentation.